ENHANCING SMART FARMING WITH CONTAINERIZED DEEP LEARNING AND KUBERNETES: UTILIZING HIPPOPOTAMUS OPTIMIZED ATTENTION MODEL FOR PREDICTIVE AGRICULTURE - Hasan, Syed Humaid; Khan, Usman Ali; Hasan, Syed Hamid; Hasan, Syeda Huyam; AlQuraishee, Anser Ghazzaal Ali (Malaysian Journal of Computer Science, 2025)
The integration of deep learning technologies into agriculture has the potential to revolutionize smart farming by enhancing efficiency, sustainability, and productivity. This study focuses on leveraging the Hippopotamus Optimized Attention Hierarchically Gated Recurrent Algorithm (HOA-HGRA) within a containerized environment to analyze and predict critical agricultural variables such as weather patterns, crop yield, and soil moisture. The proposed methodology involves containerizing deep learning models like HOA-HGRA and orchestrating them with Kubernetes on HPC clusters. This enables precise monitoring and management of crop growth, soil conditions, and livestock health, ensuring optimal resource utilization and enhanced productivity. The hyperparameters tuning and the performance optimization are performed by applying the Oppositional Hippopotamus optimization with opposition learning-based strategy. The overall performance of the AHGR-OH model is validated by utilizing the France-CGIAR BRIDGE, Smart Agriculture, Smart precision agriculture, Smart Farming Irrigation Systems, and IoT in Smart Farming Market Report datasets. Moreover, key metrics such as latency, precision, F1-score, recall, scalability, accuracy, MSE, and ROC are utilized to estimate the effectiveness of the AHGR-OH method. By comparing, the developed method grants 2s latency, 0.5 MSE, higher scalability, precision, F1-score, accuracy, and recall of 98.5%, 97.9%, 97.4%, 99.1%, and 97.9% respectively. This paper demonstrates the potential of the AHGR-OH Algorithm to revolutionize smart farming practices.